PENETAPAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN DALAM PERALIHAN HAK ATAS TANAH DI KABUPATEN ASAHAN (Tinjauan Yuridis Peraturan Daerah Kabupaten Asahan Nomor 3 Tahun 2011 tentang Bea Perolehan Hak Atas Tanah dan Bangunan) - Bahmid Bahmid (Universitas Muhammadiyah Sumatera Utara, 2016)
Tax is the largest contribution to the country as well as the implementaion of regionl autonomy. District or City expects tax as a large contribution to local revenue. One source of tax received by the state is Acquisition Duty of Right on Land and Building (Bea Hak Atas Tanah dan Bangunan (BPHTB)). Law Number 28 of 2009 concerning Regional Tax and Regional Retribution, Acquisition Duty of Right on Land and Building. Regional Regulation Number 3 of 2011 concerning Collection Procedure of Acquisition Cost. District Head Regulation Number 16 of 2011 concerning Acquisition Duty of Right on Land and Building in Asahan. Taxable object of BPHTB is acquisition duty of right on land and building. In Application, to knowing and explaining even giving evaluation how to calculate the cost of acquisition duty of right on land and building based on Regional Regulation of Asahan Number 3 of 2011 concerning Acquisition Duty of Right on Land and Building.